KDRT Dalam Perspektif Mufasir Kontemporer - Jannah, Miftahul (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The main issues studied in this research are the opinions of contemporary mufassir regarding domestic violence in the family, and the interpretation of Surah an-Nisa' verse 34 regarding violence against women in the family. Domestic violence is still a huge polemic in society. And it requires serious understanding both in terms of law and in terms of religious understanding based on the Koran and Hadith. This article discusses the views of contemporary commentators on Islamic religious Laws regarding violence against women in the household through massages in the Al-Qur'an surah an-Nisa' verse 34. Wich provides an understanding that it is permissible to hit women on condition that they are women. This violates religious orders.